Reading Peel. (17th October 2007) - Garner, Ken
John Peel: Margrave of the Marshes, John Peel and Sheila Ravenscroft (2005) London: Transworld, 420 pp., ISBN 0-593-05252-8 (hbk), 18.99John Peel: A Life in Music, Michael Heatley (2004) London: Michael O'Mara Books, 224 pp., ISBN 1-84317-157-0 (pbk), 6.99John Peel: A Tribute to the Much-Loved Broadcaster, Mick Wall (2004) London: Orion Books, 232 pp., ISBN 0-75287-212-5 (hbk), 14.99